2016
DOI: 10.1111/1750-3841.13381
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of 2‐Amino‐1‐methyl‐6‐phenylimidazo [4,5‐b]pyridine (PhIP) Formation by Alkoxy Radical Scavenging of Flavonoids and Their Quantitative Structure–Activity Relationship in a Model System

Abstract: The inhibitory effect of 10 flavonoids on the formation of 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) in a creatinine-phenylalanine model system was investigated through electronic spin resonance and a quantitative structure-activity relationship. Alkoxy radicals were observed during the heating process, providing evidence for a radical pathway in the formation of PhIP. The alkoxy radical scavenging capability of the flavonoids was proportional to their inhibition of PhIP formation (IC50 ). We dedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
1
10
1
Order By: Relevance
“…Some HAs are activated to genotoxicants in rat and human livers by cytochrome P450 (P450) 1A1‐ and 1A2‐mediated N ‐oxidation . The formation of HAs in food has been shown to involve free radicals, including ROS, that initiate oxidation processes, as well as pyrazine cation intermediate radicals . Chen et al .…”
Section: Inhibition Of Heterocyclic Aminesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some HAs are activated to genotoxicants in rat and human livers by cytochrome P450 (P450) 1A1‐ and 1A2‐mediated N ‐oxidation . The formation of HAs in food has been shown to involve free radicals, including ROS, that initiate oxidation processes, as well as pyrazine cation intermediate radicals . Chen et al .…”
Section: Inhibition Of Heterocyclic Aminesmentioning
confidence: 99%
“…As a diverse group of health-hazardous compounds, HAs have been identified in high-temperature processed foods, including grilled, baked, and fried meats, especially beef. 47 49,50 The formation of HAs in food has been shown to involve free radicals, 51,52 including ROS, that initiate oxidation processes, as well as pyrazine cation intermediate radicals. 53 Chen et al 54 reported that the reaction between creatinine and radicals of alkylpyridine led to the formation of MeIOx and IQ in fried ground beef.…”
Section: Inhibition Of Heterocyclic Aminesmentioning
confidence: 99%
“…Third, the presence of the conjugated carbonyl group on the C ring increases the inhibitory effect of the three flavonoids on PhIP formation. Yu et al [22] also confirmed that the hydroxyl groups on the A ring of the detected flavonoids, particularly at the ortho positions (C-5 and C-7), inhibited PhIP formation to the greatest extent. The hydroxyl groups on the B and C rings of the flavonoids may exert a certain synergistic effect with the C-5 and C-7 hydroxyl groups on the A ring, which increased the inhibitory effect on PhIP formation.…”
Section: Effects Of Additives On Phip Formation In Lamb Patties and Mmentioning
confidence: 77%
“…When higher concentrations of isorhamnetin and hispidulin were added to the models, less PhIP was generated, in the study by Zhang et al [21], isorhamnetin is considered an effective inhibitor of PhIP formation in a model system, with an IC50 (50% inhibiting concentration) values of 1.675 mg/mL. In addition, Yu et al [22] analyzed the creatinine/phenylalanine chemical model system and reported an IC50 value of isorhamnetin of 2.246 mg/mL. Similar to the present study, 0.03 mmol isorhamnetin (0.95 mg/mL) showed an inhibitory rate of 57.84% and the minor difference may be due to the heating conditions and the concentrations of precursors.…”
Section: Effects Of Additives On Phip Formation In Lamb Patties and Mmentioning
confidence: 99%
“…The PhIP concentration was determined by HPLC‐MS/MS coupled with tandem solid‐phase extraction (Si‐SCX–2‐C 18 ; Zhang and others ; Yu and others ). The solutions were purified using Si‐SCX‐2 cartridges (500 mg, 6 mL; Silicycle Inc., Quebec, Canada) coupled to Hypersep C 18 cartridges (200 mg, 3 mL; Thermo Electron Corporation, Bellefonte, Pass., U.S.A.).…”
Section: Methodsmentioning
confidence: 99%